2021
DOI: 10.1016/j.annonc.2021.08.819
|View full text |Cite
|
Sign up to set email alerts
|

1491P Assessment of psychiatric disorder in patients with metastatic breast cancer: A cross-sectional study

Abstract: Conclusions:The majority of prostate cancer patients reported at least mild anxiety and mild depression. In this analysis of real-world evidence, cancer stage, PSA at diagnosis, treatments, and side-effects, were among the factors affecting patients in several ways. The multiple determinants of emotional wellbeing of prostate cancer patients warrant more research and offer the opportunity for personalised interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our results were similar to other studies involving cancer patients which found that as psychological needs and symptoms increase the quality of life of patients decreases. [25][26][27][28] Psychological problems cause patients to have a negative view of the future, a decrease in their expectations, loss of energy, decrease in treatment compliance, and an increase in symptoms. 12,29 For this reason, nurses should plan nursing interventions with a holistic approach to patients undergoing RT, including psychosocial aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to other studies involving cancer patients which found that as psychological needs and symptoms increase the quality of life of patients decreases. [25][26][27][28] Psychological problems cause patients to have a negative view of the future, a decrease in their expectations, loss of energy, decrease in treatment compliance, and an increase in symptoms. 12,29 For this reason, nurses should plan nursing interventions with a holistic approach to patients undergoing RT, including psychosocial aspects.…”
Section: Discussionmentioning
confidence: 99%